Characterization and genetic analysis of a light- and temperature-sensitive spotted-leaf mutant in rice - Huang, Qi-Na; Shi, Yong-Feng; Yang, Yang; Feng, Bao-Hua; Wei, Yan-Lin; Chen, Jie; Baraoidan, Marietta; Leung, Hei; Wu, Jian-Li (Wiley, 2011)
A rice spotted‐leaf mutant was isolated from an ethane methyl sulfonate (EMS) ‐induced IR64 mutant bank. The mutant, designated as spl30 (spotted‐leaf30), displayed normal green leaf color under shade but exhibited red‐brown lesions under natural summer field conditions. Initiation of the lesions was induced by light and the symptom was enhanced at 33 °C relative to 26 °C. Histochemical staining did not show cell death around the red‐brown lesions. Chlorophyll contents in the mutant were significantly lower than those of the wild type while the ratio of chlorophyll a/b remained the same, indicating that spl30 was impaired in biosynthesis or degradation of chlorophyll. Disease reaction patterns of the mutant to Xanthomonas oryzae pv. oryzae were largely unchanged to most races tested except for a few strains. Genetic analysis showed that the mutation was controlled by a single recessive gene, tentatively named spl30(t), which co‐segregated with RM15380 on chromosome 3, and was delimited to a 94 kb region between RM15380 and RM15383. Spl30(t) is likely a novel rice spotted‐leaf gene since no other similar genes have been identified near the chromosomal region. The genetic data and recombination populations provided in this study will enable further fine‐mapping and cloning of the gene.